Pengaruh rasio profitabilitas, rasio solvabilitas, dan rasio likuiditas terhadap financial distress - Putri, Rafaisya Alanza; Hendayana, Yana (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of profitability ratios, solvency ratios, and liquidity ratios on financial distress in energy sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The sample in this study was 40 (forty) companies obtained by using the purposive sampling method. The method used in this study is causal associative and the statistical method used to test the hypothesis is logistic regression analysis using the SPSS 25 application. The results show that partially the profitability ratio influences financial distress of 0.000, while the solvency ratio is 0.622 and the ratio liquidity of 0.213 has no effect on financial distress. The research also shows that the profitability ratio, solvency ratio, and liquidity ratio influence financial distress of 67.7%, and the rest is explained by other variables outside of this research model, which is 32.3%. This research is expected to serve as an enrichment consideration for companies when managing financial health to prevent financial distress and assist shareholders in considering investment decisions.